PENERAPAN MODEL PEMBELAJARAN CARD SORT UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR MATA PELAJARAN EKONOMI - Muhammad Yusuf (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2016)
The teaching and learning process in the classroom is important to determine of the quality of education in producing good graduation that can be used as an indicator of educational success. The teaching and learning process should consider various factors that support, and able to accommodate diversity of the student's ability, potential areas, the quality of the resources, facilities and infrastructure of learning and economic. The study aims to determine the economic improvement of learning outcomes by using Learning Model Card Sort, skill of teachers to manage learning / teacher activity, student activity, after learning with Learning Model Application Card Sort. Subjects were students of class XI SMA Muhammadiyah Lamongan 09 Brondong academic year 2014/2015. This research is the Classroom Action Research (CAR), which consists of 2 cycles. Data collection techniques used observation to describe the activities of students and teachers in the Teaching and Learning Activities (KBM), the test to determine student learning outcomes. Based on the analysis of data obtained in the application of learning models Card sort that the average activities of teachers in cycle 1 was 95% with an effective category. While on the second cycle increased to 98.75% with an effective category. And the activities of students in cycle 1 reached an average of 93.75% in the active category. While on the second cycle of student activity increased to 97.5% in the active category. The results of learning students in the use of learning model Card Sort increased, it can be seen from the test results in cycle 1 reached a level of completeness 75% of the total number of students by 30 students in cycle 2 level of completeness of students increased to 92.33% of the total number of students totaling 30 students. Based on the data above, it can be concluded that the activities of students and teachers in the application of learning models Card Sort categorized succeed. The results of learning students have been achieved with a percentage of 92.33%.